HUBUNGAN PENGETAHUAN DAN SIKAP TENTANG SADARI DALAM MENDETEKSI DINI KANKER PAYUDARA PADA REMAJA SISWA KELAS XI MAN 1 OKU TAHUN 2019 - Yustina Oktarida (Jurnal Kesehatan Abdurrahman, 2020)
Breast self-examination (BSE) is very beneficial for women of early adulthood. BSE can identify breast abnormalities as early as possible, more quickly detect early stage breast cancer. This study aims to determine the Relationship of Knowledge and Attitudes about BSE in grade XI adolescents in MAN 1 Baturaja. The methodology used is an analytical survey with a cross sectional approach. The population of this study were all class XI students at MAN 1 Baturaja in the 2019 academic year, totaling 161 respondents, while the sample in this study was 150 respondents who were taken using accidental sampling technique. The data were processed using the SPSS prosram. From the results of the Chi_Square test, it was found that there was a significant relationship between the knowledge of female adolescents in class XI and BSE with a significant value of ρ value = 0.002. There is a significant relationship between the attitude of teenage girls and BSE with a significant value of ρ value = 0.000. Conclusion: there is a significant relationship between the knowledge and attitudes of class XI adolescent girls with BSE. It is suggested to schools to improve health education in an effort to provide a correct understanding of breast cancer and how to check breasts properly. Pemeriksaan payudara sendiri (SADARI) sangat bermanfaat bagi para wanita usia dewasa awal. SADARI dapat mengetahui kelainan payudara sedini mungkin, lebih cepat mendeteksi kanker payudara stadium dini.Penelitian ini bertujuan untuk mengetahui Hubungan Pengetahuan dan Sikap tentang SADARI pada remaja putri kelas XI di MAN 1 Baturaja.Metodelogi yang digunakan adalah survey analitik dengan pendekatancross sectional. Populasi penelitian ini seluruh siswi kelas XI di MAN 1 Baturaja tahun pelajaran 2019 yang berjumlah 161 responden, sedangkan sampel pada penelitian ini berjumlah 150 responden yang diambil dengan menggunakan teknik accidental sampling. Data diolah menggunakan program SPSS. Dari hasil uji Chi_Square diperoleh hubungan yang bermakna antara pengetahuan remaja putri kelas XI dengan SADARI dengan nilai signifikan ρ value = 0,002. Ada hubungan yang bermakna antara sikap remaja putrid dengan SADARI dengan nilai signifikan ρ value = 0,000. Kesimpulan: ada hubungan yang bermakna antara pengetahuan dan sikap remaja putri kelas XI dengan SADARI. Disarankan kepada sekolah agar meningkatkan penyuluhan kesehatan dalam upaya memberikan pemahaman yang benar tentang kanker payudara dan cara memeriksa payudara yang baik dan benar.